BULLISH MARKETS, BEARISH FDI: AN EMPIRICAL INQUIRY INTO PAKISTAN’S ECONOMIC DIVERGENCE (Al-Aasar, 2025)
This study examines the disconnect between the stock market and foreign direct investment (FDI) inflows in Pakistan, specifically, does bullish sentiment on the Pakistan stock exchange (PSX) indicate the possibility of new foreign investment? The study utilizes qualitative research Thematic analysis and primary data from experts in the stock exchanges, policymakers, financial analysts, and investment professionals. It is complemented by policy documents and related institutional documents. The most recent study done on the PSX states that most of the new liquidity on the PSX is from domestic liquidity, and is driven by short-term portfolio flows, and speculatively traded instruments, along with policy optimism. Contrarily, inflows of FDI have and remain deeply and stably sufficient in macroeconomic stagnation, unstable politics, insecure (and quite dangerous) the political framework, and a deeply and structurally stagnant underinvestment of the Pakistan structure. The absence of demand for real investment in the stock market and the growing demand of the real sector of the economy (real sector of the economy) in the economy) parallels the absence of demand for real investment in the stock market. Finally, analysts in Pakistan's capital market conclude that investors are misled by stock market indices. These findings indicate that improving the quality of institutions, consistency of policies, and competitiveness of the real sector are more important than reliance on stock market performance when it comes to attracting FDI.